Rancang Bangun Dan Efisiensi Alat Simulasi Heat Exchanger Menggunakan Water Cooling System - Ryan Ananda Simon; Arwizet Karudin; Remon Lapisa; Andre Kurniawan (Jurnal Vokasi Mekanika (VoMek), 2025)
The water cooling system is a technology commonly used in various industrial and automotive applications to control the temperature of engines and equipment. The heat exchanger, as a key component in this system, plays an important role in efficiently transferring heat from one medium to another. This study aims to design and construct a cross-flow heat exchanger simulation tool that uses a water cooling system, as well as to measure its heat transfer efficiency. The method employed is experimental, involving the measurement of inlet and outlet temperatures of air and water fluids, along with the ambient temperature surrounding the tool. The analysis considers three variations of air velocity: 40 m/s, 50 m/s, and 60 m/s, as well as two different climate conditions, to gain a comprehensive understanding of the tool's performance under varying situations. The research results indicate that this simulation tool is highly effective, as the resulting temperatures align with expectations, thereby enhancing the accuracy of heat transfer analysis. These findings not only benefit mechanical engineering students studying cross-flow heat exchangers as a practical study but also contribute to further developments in the field of heat transfer. This research is expected to serve as a foundation for future studies in the design and optimization of cooling systems and the improvement of efficiency in various industrial applications